Mechanism analysis of the enhanced corrosion resistance of the Mg–2Y alloy after Mn addition - Jinhang Dong; Yuxiu Zhang; Jun Liang; Zonghui He; Xiangbin Li; Fei Long (Journal of Materials Research and Technology)
In this work, the corrosion behaviors of Mg–2Y-xMn (x = 0, 0.5, 1 wt%) alloys in 3.5 wt% NaCl solution were investigated. The hydrogen volume and weight loss after immersion for the same time significantly decreased with increasing Mn content. In addition, the results of the electrochemical tests revealed that the Mn-containing alloys had a much lower corrosion current density than the Mg–2Y alloy did, indicating that the addition of Mn effectively reduced the corrosion rate. Specifically, the corrosion rate decreased from 4.91 mm y−1 in the Mg–2Y alloy to 0.81 mm y−1 in the Mg–2Y-0.5Mn alloy and to 0.48 mm y−1 in the Mg–2Y–1Mn alloy. The initial microstructures indicated that grain size, texture and dislocation barely influenced the corrosion behavior; the enhanced corrosion resistance caused by Mn addition could be well understood for two reasons. The first reason was that the addition of Mn obviously decreased the heterogeneity of the overall potential distributions in the form of Mn atoms dissolved in the Mg matrix, which reduced the possibility of galvanic corrosion. The second reason was that the corrosion product films became more stable and compact after the addition of Mn, which was filled by the MnO and MnO2 layers and could effectively retard corrosion attack in the corrosive environment. As a result, the Mn-containing alloys had much better corrosion resistance than the Mg–2Y alloy did and the Mg–2Y–1Mn alloy had the highest corrosion resistance.